The ICT sector in economic development of the countries of Eastern Europe: a comparative analysis - Dubyna, M.; Kholiavko, N.; Zhavoronok, А.; Safonov, Yu.; Krylov, D.; Tochylina, Yu. (WSEAS Transactions on Business and Economics, 2022)
The purpose of the article is to study the impact of the ICT sector on economic development of countries based on the comparative analysis of this sector development in some Eastern European countries. Within the article, economic development of the outlined countries in 2010-2019 was studied and analyzed. The analysis of the impact of the ICT sector on the GDP formation allowed to single out certain groups of countries under this indicator and to identify the characteristics that are inherent to them. Using the correlationregression analysis made it possible to analyze the ICT impact on economies development of Hungary, Bulgaria, Poland, Romania, Slovakia and the Czech Republic. Authors paid a special attention to the study of the influence of various factors on the ICT sector development. Accordingly, an analytical study of the dependence of the ICT sector weight in the GDP of the countries on the following parameters: enterprises that employ ICT specialists; enterprises that provided training to develop/upgrade ICT skills of their personnel; percentage of the ICT personnel in total employment; using Internet for Internet banking, % of individuals; enterprises who have ERP software package to share information between different functional areas; enterprises selling online (at least 1% of turnover), % of enterprises; online purchase in the last 12 months, % of individuals; enterprises having received orders via computer mediated networks, % of enterprises. Within the article, the features of the ICT sector development in the COVID-19 context are examined, and it is analyzed how the pandemic has affected the development of this sector in long and short terms. The study showed that the ICT sector today already plays a key role in the development of the national economies. Countries where the sector is developing faster show better performance and economic development.
Keywords: information and communication technologies, national economy, information technologies, economic development, digitalization, digital services